THE EFFECT OF PERCEIVED BENEFITS, CONSUMER TRUST AND PROMOTION ON INTEREST IN USE AND ITS IMPACT ON LOYALTY OF OVO APPLICATION USERS: (Case Study on Students of the Faculty of Economics, Universitas Negeri Jakarta) - Yuliansyah, Ardian Ridho; Mukhtar, Saparuddin; Sebayang, Karuniana Dianta Arfiando (Transpublika Publisher, 2022)
This study aimed to determine the impact of perceived benefits, consumer trust, and promotion on student interest in using OVO applications and their effect on user loyalty at the Faculty of Economics, Universitas Negeri Jakarta. This study employs a quantitative method of associational research. Respondents in this study were students using the OVO application at the Faculty of Economics, State University of Jakarta, and non-probability sampling with the purposive sampling technique was utilized. This study's sample consisted of 150 respondents who utilize the OVO application. With the aid of the SPSS 26 software and a multiple linear analysis method, questionnaire-obtained data were analyzed using a multiple linear analysis approach. This study employs a Likert scale and path analysis for its scale. The findings of this study indicate that the Perceived Benefits and promotions has a significant positive effect on the desire of students at the Faculty of Economics, State University of Jakarta to use the OVO application. Meanwhile, consumer trust has no effect on students' desire to use the OVO application at the Faculty of Economics, Universitas Negeri Jakarta. Likewise, student interest in using the OVO application indicates that perceived benefits have a significant impact on user loyalty. Student interest in utilizing the OVO application at the Faculty of Economics, Universitas Negeri Jakarta demonstrates that promotion has an effect on user loyalty. Meanwhile, consumer trust has no effect on user loyalty as measured by students' desire to use the OVO application at the Faculty of Economics, Universitas Negeri Jakarta. Lastly, the variable of interest in use influences positively the loyalty of OVO application users to students at the Faculty of Economics, Universitas Negeri Jakarta.